Interpretation of routine and sleep EEG: Minimum recording standards of the International Federation of Clinical Neurophysiology and the International League Against Epilepsy (2023) - YU Min, ZHU Jiang, WANG Xiaoli, ZHANG Wenjuan, LIU Yonghong (精准医学杂志, 2024)
Establishing the minimum recording standards for routine and sleep EEG is of great importance for both clinical practice and scientific research, and the joint working group of the International Federation of Clinical Neurophysiology (IFCN) and the International League Against Epilepsy (ILAE) developed the standard guideline to guide clinical practice and ensure the quality of EEG studies. This article gives an interpretation of the guideline from the aspects of the indications, technical standards, recording duration, sleep deprivation, and activation methods for EEG, in order to provide feasible standards for EEG examination in China and promote the standardization of routine and sleep EEG examination.